Role of Serum IFN-γ and IL-10 as Predictive Biomarkers of Vitiligo Disease Activity: A Case-Control Study - Karishma Desai; Hari Kishan Kumar Yadalla (Wolters Kluwer Medknow Publications, 2024)
Background and Objectives: IFNγ is a pleiotropic cytokine and through the regulation of immunologically relevant genes, they coordinate a wide range of cellular programs.[1] As a potent pro-inflammatory cytokine, it plays a pivotal role to induce depigmentation in vitiligo. In this study, we aim to assess the role of IFNγ in the activity, duration and extent of the disease and the antagonistic action of IL-10 is also assessed in vitiligo. Materials and Methods: A case-control study was conducted with 100 study participants with 50 cases clinically diagnosed as Vitiligo and 50 controls. All patients underwent complete evaluation with detailed demographic parameters, history and physical examination. The severity of the disease was assessed clinically by Vitiligo Area Scoring Index (VASI) and Vitiligo Disease Activity Score (VIDA). And blood investigations done were IFN-γ and IL-10. Results: We observed significantly higher levels of serum IFNγ levels in the patient group when compared with those of the normal controls (p=0.002) and showed a positive correlation with the activity and severity of the disease with a significant VASI (p=0.05) and VIDA score (p=<0.001). The mean serum IL-10 (p<0.001) in patients with vitiligo was significantly lower than that in the control group. Conclusion: This study showed significantly high serum levels of IFN-γ and correspondingly low levels of IL-10. New strategies, such as the combination of IFNγ blockade with inhibition of other signalling pathways, may further improve IFNγ targeted immunotherapy of the disease.